2018
DOI: 10.1002/jcb.28290
|View full text |Cite
|
Sign up to set email alerts
|

Identification of core genes and outcomes in hepatocellular carcinoma by bioinformatics analysis

Abstract: Hepatocellular carcinoma (HCC) is the most common malignant liver disease in the world. However, the mechanistic relationships among various genes and signaling pathways are still largely unclear. In this study, we aimed to elucidate potential core candidate genes and pathways in HCC. The expression profiles GSE14520, GSE25097, GSE29721, and GSE62232, which cover 606 tumor and 550 nontumour samples, were downloaded from the Gene Expression Omnibus (GEO) database. Furthermore, HCC RNA-seq datasets were also dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…Genomic, epigenetic and transcriptional alterations, as well as subsequent multistep processes, play crucial roles in the occurrence, development, metastasis and prognosis of HCC (Dhanasekaran et al, 2019;Llovet et al, 2018). Combined with public biological databases (e.g., GO and KEGG), the development of high-throughput detection technology provides us with an opportunity to systematically explore ''interesting'' gene lists on a genome-wide scale and sort out correlative biological processes (Shan, Chen & Jia, 2019; Shen et al, 2019). To identify reproducible and robust genetic alterations, integrated analyses based on multiple datasets gradually replace single cohort analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic, epigenetic and transcriptional alterations, as well as subsequent multistep processes, play crucial roles in the occurrence, development, metastasis and prognosis of HCC (Dhanasekaran et al, 2019;Llovet et al, 2018). Combined with public biological databases (e.g., GO and KEGG), the development of high-throughput detection technology provides us with an opportunity to systematically explore ''interesting'' gene lists on a genome-wide scale and sort out correlative biological processes (Shan, Chen & Jia, 2019; Shen et al, 2019). To identify reproducible and robust genetic alterations, integrated analyses based on multiple datasets gradually replace single cohort analyses.…”
Section: Discussionmentioning
confidence: 99%
“…STRING (https://string-db.org/) is a user-friendly online system that provides predicted and experimental interactions of proteins [25]. We used the STRING database to analyze functional interactions between the overlapping DEGs with a confidence score of ≄0.4 for significant differences.…”
Section: Construction Of the Ppi Network Of The Overlapping Degsmentioning
confidence: 99%
“…DTL and MCM2 were also identified as hub genes for HCC in another study (Sang, Wang, Xu, & Zhao, 2018). Shen S (Shen et al, 2019) identified FEN1 and RFC4 as core genes by analyzing four HCC datasets. The above studies indicated the core genes screened and identified in our study were of value.…”
Section: Discussionmentioning
confidence: 98%